Problem tożsamości Słowian - Lewandowski, Edmund (Zeszyty Wiejskie, 2010)
In the mental sense Slavic people exist, as they tend to think, as a separate ethnical formation and they are perceived this way in the world. In this sense the Slavic are associated mainly with Russians, Belarusians, Ukrainians and Serbs. However, in an ethnological sense some cultural features that are common for theses nations should be mentioned. In their own as well as in others‟ opinions the Slavic are unpredictable, they dislike rationalism and rules and are prone to anarchy. They do not feel a sense of moderation, they want to create by means of words, they count on miracles and gifts and they prefer suffering to effort. They act faster than they think, they take desires for reality and abuse alcohol. They attach importance to intangible matters, they like to show off courage and extravagance, they are susceptible to group parole and they tolerate mediocrity. Maybe these are the features constituting their ideal type and elements of collective identity?